1998
DOI: 10.2307/1132272
|View full text |Cite
|
Sign up to set email alerts
|

Children's Emerging Regulation of Conduct: Restraint, Compliance, and Internalization from Infancy to the Second Year

Abstract: We examined emergent regulation of conduct from infancy to the second year. Multiple observational measures at home and in the laboratory assessed, at 8-10 months, the child's restraint and attention (N = 112), and at 13-15 months, compliance to mother, internalization of her prohibition, and quality of motivation in the mother-child teaching context (N = 108). We replicated the findings previously reported for older children that supported our view of compliance and noncompliance as heterogeneous: Committed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
143
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(157 citation statements)
references
References 0 publications
9
143
1
4
Order By: Relevance
“…Each 30-sec segment was coded for the predominant quality of child compliance or noncompliance. The coding categories developed by Kochanska and her colleagues consist of five mutually exclusive codes: committed compliance, situational compliance, passive noncompliance, overt resistance, and defiance [see Kochanska et al (1998) for further details about this coding scheme]. Given that situational compliance was fairly common at both 18 and 24 months and did not predict any later outcome, it was dropped from analyses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each 30-sec segment was coded for the predominant quality of child compliance or noncompliance. The coding categories developed by Kochanska and her colleagues consist of five mutually exclusive codes: committed compliance, situational compliance, passive noncompliance, overt resistance, and defiance [see Kochanska et al (1998) for further details about this coding scheme]. Given that situational compliance was fairly common at both 18 and 24 months and did not predict any later outcome, it was dropped from analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Child compliance with parental rules is viewed as the first step in the gradual developmental shift from external to internal control of behavior. In this view, compliance is important as a precursor to conscience development (Kochanska et al, 1998). Researchers have established that compliance with rules of conduct emerges during the second year of life (Smetana et al, 2000).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Nigg et al (2004) believes that some of these regulatory behaviors rely on attention, as captured in the regulatory construct of effortful control. Kochanska, Tjebkes, & Forman (1998) suggested that easily frustrated infants are more likely to have shorter attention spans and longer latencies to organize a response requiring focused attention. Calkins et al (2002) concludes that difficulties in the control of attention and the ability to sustain attention may be related to frustration reactivity.…”
Section: Introductionmentioning
confidence: 99%